On a Boussinesq Capillarity System: Hamiltonian Reductions and Associated Quartic Geometries. Issue 1 (23rd May 2013) - Rogers, C.; Schief, W. K.
<x xml:space="preserve">Abstract</x> A nonlinear Boussinesq‐type capillarity model system is shown to admit exact reductions to coupled Hamiltonian subsystems associated with time‐modulated quartic density distributions. In particular, in 3+1 dimensions, time‐modulated "red blood cell" geometries for the density distribution are isolated.